Prevalence of Parasites in Fresh Vegetables from Two Regions of Thi-Qar Province, Iraq - Hanaa Daaj Khalaf Al-Mozan; Khalid Majeed Dakhil (Journal of Pure and Applied Microbiology, 2019)
To detect parasitic contamination of fresh vegetables and to know the extent of relationship between the prevalence of parasites on vegetables and its infection rate in the hospitals and the extent of vinegar effect (5% Acetic acid) to kill the parasites, (128) samples of six different fresh vegetable types such as Garden Cress, Leek, Radish, Lettuce, Celery and Basil. And (30) additional samples from Leek were collected from local markets of two cities in Thi-Qar province. Sedimentation technique was used for samples examination. Giardia lamblia with (71.1 %) was the dominant parasite of protozoa and Ascaris lumbricoides (15.6%) was the common parasite of helminthes therefore the significant differences were found by using the statistical analysis (T- test) in level P< 0.05. One hundred and thirteen (113) samples were contaminated with parasites, Leek and Basil with rate (100%) were full contamination with parasites while Lettuce (70%) was the lower. The direct relationship wasn’t found between percentage of parasites contamination for fresh vegetables in sale markets and percentage of intestinal parasitic infections in hospitals that near of its. There was relationship between the higher rate of prevalence G. lamblia and E. histolytica on fresh vegetables and infection of these parasites in the hospitals. No significant differences between rate of infection for male and rate of infection for female by using (T- test) in level P< 0.05. There were some parasites such as Diphyllobotherium latum, Schistosoma japonicum, Heterophyes heterophyes that are rarely or not found in Iraq were isolated from contaminated samples and this indicates to irrigation it by water contaminated with sewage or fertilization it with faces of foreign people that coming to work in Iraq and biodiversity upset and occurrence of new species did not exist in Iraq at the expense of other types. There was positive effect for vinegar (5% Acetic acid) to kill the most parasites except cysts of G. lamblia and ova of E. vermicularis.